(Invited) Fabrication and Applications of High-Efficiency, Lightweight, Multi-Junction Solar Cells by Epitaxial Liftoff. (10th April 2015) - Elarde, Victor Christopher; Miyamoto, Haruki; Chan, Ray; Stender, Chris; Youtsey, Chris; Adams, Jessica G J; Wibowo, Andree; Tatavarti, Rao; Osowski, Mark; Pan, Noren
Abstract : MicroLink Devices has developed an epitaxial liftoff (ELO) technology for removing thin device layers from the surface of a semiconductor wafer using a flexible metallic sheet to provide structural support. The wafer is left intact and available for use in a subsequent growth cycle. This technology has been applied to high-efficiency, multi-junction solar cells. Removal of the substrate allows the devices to achieve very high specific power of approximately 1000W/kg. For large area devices, the cost of the substrate can be a significant component of the overall device manufacturing cost. By utilizing ELO technology to reuse the substrate for multiple growth cycles, the manufacturing cost of the device can be dramatically reduced.